Hambatan Integrasi Komunikasi Interaktif Antar Tim Bisnis Dan Tim Publikasi Dalam Mendapatkan Keuntungan Melalui Program Deureuham Pada Bank X Syariah Kantor Pusat Tahun 2018-2019 - Sri Reni Musfita; Rosmawaty Hilderiah Pandjaitan (ArtComm, 2021)
Deureuham program is the result of collaboration between Bank X Syariah and BEKRAF, consisting of a Publication Team and a Business Team as the responsible party and communicate interactively through the WhatsApps Group media. Ironically, the program did not generate profits as targeted. This is the rationality of the reasons, as well as the urgency of this research, so that the title of this research is determined, namely, the obstacles to the integration of interactive communication between the business team and the publication team in getting benefits through the Deureuham program at Head Office Bank X Syariah on 2018-2019. This qualitative research uses case study as a method, with a constructivist paradigm. The theoretical foundation is the Kincaid school of convergence theory and the Karl Weick Organizational Process Theory, the data collection technique is by means of in-depth interviews. As a result: One, the obstacles to the integration of interactive communication between the two teams, namely, a lack of communication processes, a lack of a sense of belonging and shared responsibility, and poor information shared, including dialogue between teams. Two, the result is poor processes and information flow between teams, confusion of information, and a low sense of responsibility for each team, information is not conveyed optimally, and low business absorption rates. Three, the input is that coordination is not only through interactive media, but also face-to-face meetings. The use of interactive media is maximized internally for each team. In order to avoid confusion of information, it is necessary to involve branches in interactive communication between teams, as well as the need to control the progress of communication from the superiors of each team.